Ancient divergence and recent population expansion in a leaf frog endemic to the southern Brazilian Atlantic forest - Brunes, Tuliana O.; Thomé, Maria Tereza C. [UNESP]; Alexandrino, João; Haddad, Célio F. B. [UNESP]; Sequeira, Fernando (Springer Nature, 2015)
The evolutionary history of Neotropical organisms has been often interpreted through broad-scale generalizations. The most accepted model of diversification for the Brazilian Atlantic forest (BAF) rely on putative historical stability of northern areas and massive past habitat replacement of its southern range. Here, we use the leaf frog Phyllomedusa distincta, endemic to the southern BAF, to better understand diversification patterns within this underexplored rainforest region. We used an integrative approach coupling fine-scale sampling and multilocus sequence data, with traditional and statistical phylogeographic (multilocus approximate Bayesian computation) methods to explore alternative hypotheses of diversification. We also employed species paleodistribution modeling to independently verify habitat stability upon a spatially explicit model. Our data support two divergent lineages with coherent geographic distribution that span throughout northern and southern ranges. Demographic estimates suggested the Southern lineage has experienced a recent population expansion, whereas the Northern lineage remained more stable. Hypothesis testing supports a scenario of ancient vicariance with recent population expansion. The paleodistribution model revealed habitat discontinuity during the Last Glacial Maximum (LGM) with one area of putative stability within the range of the Northern lineage. Evidence on genetic structure, demography, and paleodistribution of P. distincta support a historically heterogeneous landscape for the southern BAF, with both areas of forest stability and regions where forest occupation is probably recent. We also associate the southern end of the Cubatão shear zone with a phylogeographic break in the BAF. Taken together, our results argue for the idea of multiple mechanisms generating diversity in this biome and underscore the need of fine-scale data in revealing more detailed pictures.
Keywords: Amphibians; Approximate Bayesian computation; Diversification; Multilocus; Paleodistribution modeling; Phylogeography